PENERAPAN METODE PROBLEM BASED INSTRUCTION (PBI) BERBANTUAN MEDIA YOUTUBE DALAM PEMBELAJARAN MENULIS CERPEN SISWA SMA NEGERI 9 KOTA JAMBI - Zahra Aulia Islami; Afif Rofii; Abdoel Gafar (Universitas Batanghari, 2026)
This study to determine the effectiveness of the application of the Problem Based Instructions (PBI) method assisted by YouTube video media in learning to write short stories for grade XI Phase F students of SMA Negeri 9 Kota Jambi in the 2025 Academic Year. This study uses a quantitative approach with a quasi-experimental method and a one-group pretest-posttest design. The research subjects were 34 students selected using a purposive sampling technique. The research data were obtained through a short story writing test given before (pretest) and after (posttest) the application of the problembased instruction (PBI) method assisted by YouTube video media. The assessment was carried out using a rubric that includes the structure of the short story, intrinsic elements, language style, creativity, and language accuracy. Data analysis was carried out through prerequisite tests (Shapiro-Wilk normality test and Levene's Test homogeneity test) and hypothesis testing using the Paired Sample t-Test with the help of the SPSS program. The results of the prerequisite test showed that the data were normally distributed and had homogeneous variance. The t-test results showed a calculated t-value of 9.672, which is greater than the t-table value of 2.0345, with a significance level of 0.000 < 0.05. Therefore, H₀ is rejected and Hₐ is accepted. This means there is a significant difference between the pretest and posttest scores in students' short story writing skills. Therefore, it can be concluded that the application of the PBI method assisted by YouTube videos is effective in improving students' short story writing skills.